Trade Facilitation and Country Size - Amin, Mohammad (World Bank, Washington, DC, 2014)
It is argued that compared with large countries, small countries rely more on trade and therefore they are more likely to adopt liberal trading policies. The present paper extends this idea beyond the conventional trade openness measures by analyzing the relationship between country size and the number of documents required to export and import, a measure of trade facilitation. Three important results follow. First, trade facilitation does improve as country size becomes smaller; that is, small countries perform better than large countries in terms of trade facilitation. Second, the relationship between country size and trade facilitation is nonlinear, much stronger for the relatively small than the large countries. Third, contrary to what existing studies might suggest, the relationship between country size and trade facilitation does not appear to be driven by the fact that small countries trade more as a proportion of their gross domestic product than the large countries.